2016
DOI: 10.1007/s10877-016-9940-7
|View full text |Cite
|
Sign up to set email alerts
|

Determination of saturation, heart rate, and respiratory rate at forearm using a Nellcor™ forehead SpO2-saturation sensor

Abstract: Alterations in arterial blood oxygen saturation, heart rate (HR), and respiratory rate (RR) are strongly associated with intra-hospital cardiac arrests and resuscitations. A wireless, easy-to-use, and comfortable method for monitoring these important clinical signs would be highly useful. We investigated whether the Nellcor™ OxiMask MAX-FAST forehead sensor could provide data for vital sign measurements when located at the distal forearm instead of its intended location at the forehead to provide improved comf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…We also found that obtaining heart rate, SpO 2 , and respiration within an acceptable degree of accuracy was also possible at a single tested anatomical location at rest, the finger. The use of both reflective and transmissive PPG for pulse oximetry on the finger is well accepted and has been demonstrated in numerous publications [12,22,23]. The results in this study for the finger pulse oximetry at rest concur with the literature.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We also found that obtaining heart rate, SpO 2 , and respiration within an acceptable degree of accuracy was also possible at a single tested anatomical location at rest, the finger. The use of both reflective and transmissive PPG for pulse oximetry on the finger is well accepted and has been demonstrated in numerous publications [12,22,23]. The results in this study for the finger pulse oximetry at rest concur with the literature.…”
Section: Discussionsupporting
confidence: 87%
“…While many studies have been previously conducted into the placement of PPG sensors for pulse oximetry [5,10,11,12,13,14,15,16,17], few studies have been conducted for a suitable location to collect heart rate, SpO 2 , and respiration. Kramer et al [10] developed a new pulse oximeter for use at non-traditional anatomical locations for the measurement of heart rate, SpO 2 , and respiration.…”
Section: Introductionmentioning
confidence: 99%
“…The application of wrist-wearable devices are possible in different domains: medicine—to monitor a patient’s health (as well as activity and environmental parameters) in order to prevent injuries and allow for the early detection of illnesses and/or disorders as well as early interventions, offer preventive actions to avoid the deterioration of a health condition [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]; risky professions (such as construction, firefighting, aviation, and military)—to monitor a person’s vital health functions (as well as activity and environmental parameters) to prevent potential risky situations such as accidents and injuries and offer corrective or preventive actions to be undertaken to avoid further deterioration or risk [ 10 , 33 , 34 , 35 , 36 , 37 , 38 ]; education—monitoring stress levels and health conditions to offer personalized learning plans, time management recommendations, the scheduling and development of classroom activities, and establishing students’ working groups [ 2 , ...…”
Section: Introductionmentioning
confidence: 99%
“…medicine—to monitor a patient’s health (as well as activity and environmental parameters) in order to prevent injuries and allow for the early detection of illnesses and/or disorders as well as early interventions, offer preventive actions to avoid the deterioration of a health condition [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ];…”
Section: Introductionmentioning
confidence: 99%
“…Recent development in wrist-based fitness monitors and their improved measurement capability also during movements makes it tempting to target their use to hospital patients (El-Amrawy and Nounou 2015). Some reports exist on the use of such devices on hospitalized patients (Harju et al 2017), but the evidence on their reliability and accuracy in association to rhythm abnormalities is still very limited. The performance of sensors based on the use of green wavelengths seems most promising during movement (Lee et al 2013a, Matsumura et al 2014.…”
Section: Introductionmentioning
confidence: 99%